L-DOPA Improves Ventilation but Not the Ventilatory Response to Hypercapnia in a Reserpine Model of Parkinson’s Disease - Monika Jampolska; Kryspin Andrzejewski; Paweł M. Boguszewski; Katarzyna Kaczyńska (Brain Sciences, 2023)
Parkinson’s disease (PD) is a neurological disorder characterized by progressive degeneration of the substantia nigra that affects mainly movement control. However, pathological changes associated with the development of PD may also alter respiration and can lead to chronic episodes of hypoxia and hypercapnia. The mechanism behind impaired ventilation in PD is unclear. Therefore, in this study, we explore the hypercapnic ventilatory response in a reproducible reserpine-induced (RES) model of PD and parkinsonism. We also investigated how dopamine supplementation with L-DOPA, a classic drug used to treat PD, would affect the breathing and respiratory response to hypercapnia. Reserpine treatment resulted in decreased normocapnic ventilation and behavioral changes manifested as low physical activity and exploratory behavior. The respiratory rate and the minute ventilation response to hypercapnia were significantly higher in sham rats compared to the RES group, while the tidal volume response was lower. All of this appears to be due to reduced baseline ventilation values produced by reserpine. L-DOPA reversed reduced ventilation, indicating a stimulatory effect of DA on breathing, and showed the potency of DA supplementation in restoring normal respiratory activity.